The Assessment of Hapanasan Hot Spring Nature Tourism Based on the Analysis of Working Areas for Nature Tourism Objects and Attractions - Siti Kholizah; Rahmawaty; Hamdani Harahap; Mohd Hasmadi Ismail (Talenta Publisher, 2024)
Hapanasan Hot Spring Nature Tourism (HHSNT) is located in Rambah Tengah Baru Village, Rambah Sub-district, Rokan Hulu District, Riau Province. The area of HHSNT is 9 ha. This research aims to identify existing facilities in this area and assess the attractiveness, accessibility, environmental conditions, accommodation, infrastructure, and availability of clean water at this nature tourist location. In-depth interviews were conducted with 13 key informants. Direct observation was carried out by systematically observing and recording this region's potential nature tourist attractions. The analysis of working areas for nature tourism objects and attractions (Analisis Daerah Operasi-Objek Daya Tarik WisataÂ Alam/ADO-ODTWA) is used to determine the feasibility value of this tourist attraction. The results of this research show that the criteria value for attractiveness is 83.33%, the criteria for accessibility is 95.83%, the criteria for accommodation is 83.33%, the criteria for supporting facilities and infrastructure is 80%, the criteria for availability of clean water is 73.88%, and the criteria for socio-economic environmental conditions is 66.66%. Overall, the HHSNT area is worthy of development, with a percentage of 80.50%. The development of HHSNT can bring numerous benefits to the community, economy, and environment of Rokan Hulu. It can contribute to sustainable development while preserving the region's nature and cultural heritage for future generations